Aspirin attenuates monocrotaline-induced pulmonary arterial hypertension in rats by suppressing the ERK/MAPK pathway. (2nd January 2017) - Gao, Hua; Cheng, Yuqing; Zong, Liguo; Huang, Linian; Qiao, Chenchen; Li, Wei; Gong, Beilei; Hu, Junfeng; Liu, Haitao; Wang, Xiaojing; Zhao, Chengling
ABSTRACT: This study aimed to investigate the therapeutic effects of aspirin (ASA) and its potential mechanisms of action in monocrotaline (MCT)-induced pulmonary arterial hypertension (PAH) in rats. PAH was induced in a rat model by a single intraperitoneal (IP) injection of MCT. Saline was injected in a control group. Two weeks following MCT injection, right ventricular systolic pressure (RVSP) and systolic blood pressure (SBP) were measured in six rats from each group to confirm establishment of a PAH model. The remaining MCT-treated rats were randomly allocated to receive IP injection of saline, ASA, or ERK1/2 inhibitor PD98059. Four weeks following treatment, RVSP was measured and all rats were sacrificed for histological study. There was no significant difference in SBP in any group two weeks following MCT administration. Nonetheless RVSP was significantly increased in the MCT group compared with the control group. At 6 weeks, ASA treatment remarkably attenuated MCT-induced increased RVSP, RV hypertrophy, and pulmonary artery remodeling compared with the MCT group. The density of pulmonary capillaries in ASA-treated rats was also dramatically increased. Treatment with ASA significantly inhibited the increased p-ERK1/2 and restored the impaired endothelial nitric oxide synthase (eNOS) in MCT-treated rats. This study demonstrated that ASA distinctively attenuates MCT-induced PAH by inhibition of the ERK1/2 signaling pathway.